Louisa was solving the following equation:
17j + 22 = -23 + 2j
To join like terms, she should 'pass' the -23 to the left side of the equation.
So, she added 23 on both sides and got:
17j + 22 + 23 = -23 + 23 + 2j
Now we operate the numbers on each side:
17j + 45 = 2j
Note the 23 and the -23 canceled out.
That was doubtless what Loisa did in her first step
Now for the second step
To join the j's, now she must 'pass' the 17j to the right side. She did it by subtracting 17j on both sides of the equation as follows:
17j - 17j + 45 = 2j - 17j
Operating the terms with j's:
45 = -15j
Note the 17j and -17j were canceled out, and the right side was simplified
The logic third step should be to divide the equation by -15:
45/(-15) = j
Dividing:
-3 = j
Or, j = -3 is the solution of the equation